Design of tri-band flexible CPW 4-port slot MIMO antenna for conformal 5G, WIFI 6/6E and X-band applications - Chengzhu Du; Fangrui Zhang; Ruomeng Li (Engineering Science and Technology, an International Journal)
In this paper, a tri-band flexible CPW 4-Port slot MIMO antenna is devised according to the requirements of 5G communication systems for signal transmission, which can be applied to 5G N77/78(3.3–4.2 GHz), WIFI6/6E (5.15–5.83 GHz,5.925–7.125 GHz) and X-band (8.5–10.68 GHz) satellite communication. Four slot antennas are placed orthogonally, and the high isolation of the antenna is achieved by isolated branches made of crossed branches and circles. The antenna is fabricated on a flexible dielectric substrate, and the bending test and human body test results meet the specified requirements. The measurement results indicate that the operating bands are 3.0–4.46 GHz, 5.07–7.15 GHz and 8.01–12 GHz, the port isolation (S21, S31) is better than 25 dB, and the envelope correlation coefficients (ECC) are all less than 0.01, which indicate that the antenna has a broad application prospect in the field of wearable 5G and future 6G communication.